Expert System Diagnosis of Skin Disease in Cat with Forward Chaining Method - Ais Achmad Sutrisna; Sidik Sidik; Indra Riana Rahajeng; Muhamad Ryansyah (Jurnal Mantik, 2021)
An expert system on cat skin is a system that is intended for cat owners in which there are several problems that often occur based on observations of complaints that often occur for cat owners, from these problems I have conducted a research on several doctors to find solutions to some of the problems that I have researched, from the various problems that I have found I propose to create an expert system for skin diseases in cats with a Web-based forward chaining method. This forward chaining method is expected to make it easier for users to find out what skin diseases are being experienced by cats based on the rules that have been applied in the form of choices from various questions that have been presented to the user to achieve the goal in the form of output results (Consultation Results Report). So in the consultation report the user can find out what skin disease is being suffered by the cat and there are also consultation results that encourage the user to follow up for a direct consultation with the doctor.